String cosmology and inflation. - Angelantonj, Carlo; Amendola, Luca (Arxiv, 1995)
Following a suggestion by Gasperini and Veneziano, that String Cosmology can be reconciled with Inflation and, hence, with the Standard Big Bang, we display an analytical solution which possesses four interesting properties: (1) it is non-singular; (2) it distinguishes the dynamics of the external scale factor, $a(t)$, from that of the internal one,
Gesehen am 21.11.2017